National bioethical legislation and guidelines for biomedical research in the Islamic Republic of Iran - Farzaneh Zahedi; Bagher Larijani
Rapid advances in biomedical science and technology, which have revolutionized medicine and health-care services in different societies, have been associated with inevitable ethical challenges. Undoubtedly, these innovations could lead to irreversible disasters if they are not limited by appropriate regulations. Substantial attempts have been made in the Islamic Republic of Iran to establish a structured approach for identifying, analysing and resolving ethical issues in clinical practice. Given the consensus of religious and scientific scholars, some laws recently approved by the parliament include the Deceased and Brain-Dead Patients Organ Transplantation Act (2000), Embryo Donation to Infertile Spouses Act (2003) and the Therapeutic Abortion Act (2005). National guidelines for ethical assessment and supervision of research proposals have also been compiled by the authorities. This paper reviews the main endeavours made in bioethics legislation in the Islamic Republic of Iran.